The Magic in the Image : Women in Clay at Mohenjodaro and Harappa - Ratnagar, Shereen, (Brill | Manohar Publishers & Distributors, 2018)
Hundreds of clay figurines of women, and their fragments, were found in the remains of Harappa and Mohenjo-daro, major cities of the Indus civilization, but almost none in the other Harappan towns or villages. What could be the explanation? This study begins with the background: the archaeological history, various studies of figurines, and how they came to be linked with the idea of the mother goddess. There is also an attempt to draw a general picture of popular religion of the time, and to detect archaeological traces of Harappan beliefs and religious practices. There follows an analysis of the figurines themselves: what were their antecedents? Do the few male clay figurines fall in the same genre as the plentiful remains of women's images? There were youthful women, mothers, portly matrons, and also women at the grinding stone, but nothing that could be a representation of 'womanhood'. Attention is paid to the variation in headgear, hairstyles, ornamentation, and the all-pervasive hip-girdles. Nudity is also a topic of discussion. Besides, they cannot be stood upright. As for their distribution, it was significantly irregular. Although attempts to replicate the firing of these solid objects using simple methods failed, it is doubtful to what extent they were made by skilled potters, the modelling being unpractised and even clumsy, as the photographs of some profiles, published here for the first time, shows.